Formulasi Kebijakan dalam Pelayanan Pembayaran Pajak Waris Bea Perolehan Hak Atas Tanah dan Bangunan di Badan Pendapatan Kota Palembang - Akbar, Muhammad Hamka; Putra, Raniasa; Iriani, Atrika; Abduh, Muhammad (Economic Reviews Journal, 2025)
Service is an obligation that must be carried out by the government to its citizens with community services to live prosperously and prosperously as mandated in the 1945 Constitution of the Republic of Indonesia and Law Number 1 of 1974 Article 1 concerning Marriage is a physical and spiritual bond between a man and a woman as husband and wife with the aim of forming a happy and eternal family based on the Almighty God and Law Number 25 of 2009 concerning Public Services. The mechanism of inheritance tax services for Land and Building Acquisition Fees at the Palembang City Regional Revenue Agency in accordance with Regional Regulation Number 4 of 2023 concerning Regional Taxes and Levies, inheritance is property passed down by parents to their biological children.